Sikap Masyarakat Lokal Terhadap Pengembangan Desa Wisata Taro, Kecamatan Tegallalang, Kabupaten Gianyar - Wangku, Philipus; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i01.p07, 2022)
Taro is the one tourism village In Tegallalang subdistric, Gianyar Regency. In the development of Bali tourism, there ia saturation of moderen forms of tourism and want to feel and life in rudal areas making the development of tourism in rural areas which Will be packaged in the form of tourism. Tourism Villages in Bali have not all gone smoothly so that they still need help from stakeholder in terms of developing at tourist village. Taro village ia one of the tourist village that has a variety of wonderful potential in the form of attraction, as well as tourist attractions. The porpuse of this study was to determine the existing conditions in Taro tourism village, Tegallalalng sub distric, and to find out the attitude of the local comunity in developing Taro tourism village, Tegallalalng sub distric. The research methodology used in this study ia qualitative research where this qualitative research uses observation techniques, in depth interview and documentation studies. And using the concept of 4A tourism produce, components in formulating the existing condition of Taro tourism village. The result of the study show that the existing condition of Taro tourism village starting from attractions, accessibility, fasilitas, and tourism supporting institutions are still in the development proccess, so that is requires collaboration between stakeholder d in developing Taro tourism village, and attitude of local comunities in developing Taro tourism village with using the irridex ( Irritation index) concept. Keywords: comunity attitudes, developing villages (irridex), tourism village.